2011
DOI: 10.1016/j.devcel.2011.05.012
|View full text |Cite
|
Sign up to set email alerts
|

SLIT/ROBO1 Signaling Suppresses Mammary Branching Morphogenesis by Limiting Basal Cell Number

Abstract: Summary In the field of breast biology, there is a growing appreciation for the “gatekeeping function” of basal cells during development and disease processes; yet, mechanisms regulating the generation of these cells are poorly understood. Here, we report that the proliferation of basal cells is controlled by SLIT/ROBO1 signaling and that production of these cells regulates outgrowth of mammary branches. We identify the negative regulator TGF-β1 upstream of ROBO1 and show that it induces Robo1 expression speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 54 publications
6
116
1
Order By: Relevance
“…7B). In contrast, expression of Slit-2 and Robo-1, both shown to enhance branching morphogenesis in mice upon deletion as seen in CD151-targeted mice, 45 exhibited a minimal change (Fig. 7A).…”
Section: Cd151 Removal Coincides With the Induction Of Transcription mentioning
confidence: 88%
See 1 more Smart Citation
“…7B). In contrast, expression of Slit-2 and Robo-1, both shown to enhance branching morphogenesis in mice upon deletion as seen in CD151-targeted mice, 45 exhibited a minimal change (Fig. 7A).…”
Section: Cd151 Removal Coincides With the Induction Of Transcription mentioning
confidence: 88%
“…6), even though both of these molecules have recently been shown to repress the pubertal outgrowth of mammary glands. 45 In this regard, the skewed distribution of basal or myoepithelial cells detected in CD151-targeted mice may be partially attributed to the altered function of Ron, rather than Slit-2/Robo-1 receptor complexes (Fig. 7C).…”
Section: Cd151 Mediates Normal Development Of Mammary Glands By Reprementioning
confidence: 99%
“…Even though Myc was deleted from the BCs only, luminal cells displayed decreased proliferation rates, and luminal progenitor population was diminished in mutant epithelium. A recent study provided evidence that BCs contribute to the control of mammary branching morphogenesis probably due to production of soluble growth factors stimulating proliferation of luminal cells [33]. We, therefore, suggest that a lack of paracrine or direct intercellular signaling between basal and luminal layers due to low BC number or/and impaired gene expression in Myc-deficient BCs could account for the diminished proliferation and low progenitor cell content in the luminal compartment and decreased branching complexity observed in K5cre;myc F/F mammary epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, simultaneous loss-of-function mutations of slit2 and ntn1 genes resulted in an enhanced phenotype with separated luminal and basal cell layers in the mammary ducts suggestive of synergy between Slit2 and Netrin 1 during ductal morphogenesis. A recent report from the same laboratory implicated Slit/Robo1 signaling in the control of mammary branching morphogenesis (Macias et al, 2011). The authors suggested that basal myoepithelial cells control the formation of new ductal branches via the production of mitogens for the luminal cells.…”
Section: Intercellular and Paracrine Interactions Involving Myoepithementioning
confidence: 99%
“…The authors suggested that basal myoepithelial cells control the formation of new ductal branches via the production of mitogens for the luminal cells. Macias and coworkers revealed that the TGF-b1-induced expression of Robo1 in basal myoepithelial cells and the interaction of Slit2 with Robo1 inhibited b-catenin signaling, limiting basal cell proliferation and preventing the formation of new branches (Macias et al, 2011).…”
Section: Intercellular and Paracrine Interactions Involving Myoepithementioning
confidence: 99%